Enzyme-modified particles for selective biocatalytic hydrogenation by hydrogen-driven NADH recycling. - Reeve, H; Lauterbach, L; Lenz, O; Vincent, K (Wiley, 2015)
We describe a new approach to selective H2-driven hydrogenation that exploits a sequence of enzymes immobilised on carbon particles. We used a catalyst system that comprised alcohol dehydrogenase, hydrogenase and an NAD(+) reductase on carbon black to demonstrate a greater than 98 % conversion of acetophenone to phenylethanol. Oxidation of H2 by the hydrogenase provides electrons through the carbon for NAD(+) reduction to recycle the NADH cofactor required by the alcohol dehydrogenase. This biocatalytic system operates over the pH range 6-8 or in un-buffered water, and can function at low concentrations of the cofactor (10 μm NAD(+)) and at H2 partial pressures below 1 bar. Total turnover numbers >130 000 during acetophenone reduction indicate high enzyme stability, and the immobilised enzymes can be recovered by a simple centrifugation step and re-used several times. This offers a route to convenient, atom-efficient operation of NADH-dependent oxidoreductases for selective hydrogenation catalysis.